Does Culture Matter to Pro-Social Behavior? Evidence from a Cross-Ethnic Lab Experiment - Sun, Fengwei; ., Xiaoxiao Wang; ., Quanlan Yi; ., Mengliang Wu (Journal of Economics and Behavioral Studies, 2015)
Recent investigations have uncovered large, consistent deviations from the predictions of Homo economics that individuals are entirely self-regarding. Our study undertook a cross-cultural study of behavior search for the evidences of other-regarding behaviors and its ethnic difference, and accounted for by anatomy of culture. This study recruited 90 subjects of three ethnic groups from market trade-based (ethnic Han), nomadism-based (ethnic Zang) and agriculture-based (ethnic Bouyei) areas in China and conducted public good provision experiment with stranger-treatment design. Under the assumption of self-regarding preferences, the Nash equilibrium is zero contribution by all in public account using backward induction. However, we found contributions did not reduce to zero over all three sessions. Besides, the differences in contributions between ethnicities strongly depended on the degree of ethnic dominance, and Zang harbored the strongest reciprocal preference generally over all group structures. A particular set of measurable factors was identified as proxies for cultural influences on behavioral differences observed in experiments between ethnicities. The results showed all of the cultural factors accounted for the behavioral differences between the ethnic Han and the other two minor ethnicities. However, behavioral difference between minor ethnicities was attributed to group structure only. (1) People may harbor various forms of prosocial emotions in economic affairs, and especially exhibit stronger at the initial phase rather than what canonical model assumes. (2) Behavioral differences between ethnicities are prominent and can be explained by differences in cultural influence.